(RE)CONSTRUCTION OF STUDENT MUSIC TEACHER IDENTITY - Lasauskiene, Jolanta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The professional identity of music teacher represents the essence of this profession. Improving the programmes of music teacher education and deciding how to (re)construct the professional identity of prospective music teachers, it is important to discuss what contextual factors can have an impact on the development of music teacher identity and what possibilities of its (self-) development are available at university. A better understanding of the role-identity of teachers at various stages of their careers could enhance the conceptions of study programmes in music teacher education. The article analyses and discusses the conception of music teacher identities, substantiates its peculiarities during pre-service training, points out the most important characteristics for the successful professional activity of the music teacher. The research presented in the article focuses on professional identity development of 30 university music students (15 Lithuanian and 15 foreign) at Lithuanian University of Educational Sciences (Music Education). The method of focus group interview was used in this study.The research results show that the student music teachers have developed a distinctive attitude towards the professional education in universities and their own expectations. Suggestions for practice and further research are also provided.